The Diagnostic Yield of Malignancy Comparing Cytology, FISH, and Molecular Analysis of Cell Free Cytology Brush Supernatant in Patients With Biliary Strictures Undergoing Endoscopic Retrograde Cholangiography (ERC): A Prospective Study. Issue 9 (October 2019) - Kushnir, Vladimir M.; Mullady, Daniel K.; Das, Koushik; Lang, Gabriel; Hollander, Thomas G.; Murad, Faris M.; Jackson, Sara A.; Toney, Nicole A.; Finkelstein, Sydney D.; Edmundowicz, Steven A.
Abstract : Background: Routine cytology of biliary stricture brushings obtained during endoscopic retrograde cholangiopancreatography (ERCP) has suboptimal sensitivity for malignancy. We compared the individual and combined ability of cytology, fluorescence in situ hybridization (FISH) analysis and PCR-based mutation profiling (MP) to detect malignancy in standard biliary brushings. Methods: We performed a prospective study of patients undergoing ERCP using histology or 1 year follow-up to determine patient outcomes. MP was performed on free-DNA from biliary brushing specimens using normally discarded supernatant fluid. MP examined KRAS point mutations and tumor suppressor gene associated loss of heterozygosity mutations at 10 genomic loci. FISH examined chromosome specific gains or losses. Results: A total of 101 patients were included in final analysis and 69% had malignancy. Cytology had 26% sensitivity and 100% specificity for malignancy. Using either FISH or MP in combination with cytology increased sensitivity to 44% and 56%, respectively. The combination of all 3 tests (cytology, FISH, and MP) had the highest sensitivity for malignancy (66%). There was no difference in the specificity of cytology, FISH or MP testing when examined alone or in combination. MP improved diagnostic yield of each procedure from 22% to 100%; FISH improved yield to 90%. MP detected 21 malignancies beyond that identified by cytology; FISH detected an additional 13. The combination of FISH and MP testing detected an additional 28 malignancies. Conclusions: Both MP and FISH are complimentary molecular tests that can significantly increase detection of biliary malignancies when used in combination with routine cytology of standard biliary brush specimens.